2010
DOI: 10.1002/pi.2892
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and thermal behaviour of block copolymers of polydimethylsiloxane and polyamide having trichlorogermyl pendant groups

Abstract: Block copolymers having a pendant trichlorogermyl group as a part of polyamide segment(COR′CONHArNH)xCOR′COand polydimethylsiloxane of general formula [(COR′COHNArNH)xCOR′CONH(CH2)3SiO(CH3)2 ((CH3)2SiO)ySi(CH3)2(CH2)3 NH]n (where R′ = CH2CH(GeCl3), CH(CH3)CH(GeCl3), CH(GeCl3)CH(CH3); Ar = C6H4, (C6H3CH3)2, (C6H3OCH3)2, 2,5‐(CH3)2C6H2, C6H4OC6H4) were prepared by a polycondensation reaction and characterized using CHN and Ge analysis, Fourier transform infrared (FTIR) and 1H NMR spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…The temperature of the reaction was initially maintained at 0 °C as the reaction is extremely exothermic and the highly reactive diacyl chlorides may undergo side reactions at higher temperatures distorting the molecular stoichiometry which may inhibit the chain growth . Telechelic PDMS was added at room temperature and the reaction was brought to reflux for 72 h as copolymerization reactions between incompatible segments usually require prolonged heating . THF was the solvent of choice for copolymerization as all the reactants were soluble in it and it is usually used when polymers with moderate molecular weights are required , .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature of the reaction was initially maintained at 0 °C as the reaction is extremely exothermic and the highly reactive diacyl chlorides may undergo side reactions at higher temperatures distorting the molecular stoichiometry which may inhibit the chain growth . Telechelic PDMS was added at room temperature and the reaction was brought to reflux for 72 h as copolymerization reactions between incompatible segments usually require prolonged heating . THF was the solvent of choice for copolymerization as all the reactants were soluble in it and it is usually used when polymers with moderate molecular weights are required , .…”
Section: Resultsmentioning
confidence: 99%
“…An alternative way to utilize siloxanes without chemical crosslinking is the controlled synthesis of their block copolymers . Such polymers containing polysiloxane segments covalently bonded with other types of backbones are of interest in generating new hybrid polymers . The synthesis of these copolymers is made possible because of the many organic reactive terminal groups such as amino, carboxyl, hydroxyl, epoxy etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of PDMS-PA segmented copolymers were reported that included organometallic structural features. For example, two PDMS-PA copolymers containing pendent trichlorogermyl or ferrocene groups both exhibited good thermal and mechanical properties for use as protective coatings [122,123]. However, a majority of the research conducted on PDMS-PA copolymers included PDMS poly(aramid) (PDMS-PAr) segmented copolymers that Imai et al introduced in 1989 [124].…”
mentioning
confidence: 98%
“…Policy strategies which have been employed for solubility increase in aromatic polyamides are lateral substitution and the distortion of the rigid character introducing non‐planar, kinked, or flexible parts in the main chain. Research efforts are therefore underway to take advantage of their properties, enhance their machinability, solubility, and incorporate new chemical functionalities in the polyamide backbone or lateral structure, so that their applicability is expanded and remains on the forefront of scientific research 8–10. Considering the extraordinary characteristics of the chemically simplest aramids, the research efforts are twofold directed: (i) diminishing of the cohesive energy that causes intractable materials (due to their extremely low solubility and exceptionally high thermal transitions) with little change to their high‐performance properties; and (ii) the expansion of their applications as high‐performance materials in new and promising advanced fields, such as optically active, luminescent, ionic exchange, flame resistant, and fiber‐forming materials.…”
Section: Introductionmentioning
confidence: 99%